Jurisdiction of the national industrial court of Nigeria: a critical analysis (2014)
In all known legal systems, jurisdiction is the basis on which the power of the court is premised. It is a threshold issue in the process of judicial adjudication. It is therefore fundamental principle of law that any decision reach by a court of law without jurisdiction is null, void and of no legal effect whatsoever. Due to the importance of jurisdiction, every court undertaking judicial exercise must ensure that it has jurisdiction to entertain the matter brought before it to avoid embarking on futile exercise. This paper critically examines the jurisdictions of the National Industrial Court in Nigeria. The paper recommends further amendment to the provisions of two important statutory provisions which conferred jurisdiction on the National Industrial Court: the National Industrial Court Act, 2006 and the Constitution of Federal Republic of Nigeria (Third Alteration) Amendment Act, 2010. The aim of this is to bring the operation of the Nigeria National Industrial Court in conformity with its peers the world over.